Birthplace and birthdate of Brazilian Olympic medalists - Alexandre Vinicius Bobato Tozetto; Rodolfo Silva da Rosa; Felipe Goedert Mendes; Larissa Rafaela Galatti; Edison Roberto de Souza; Carine Collet; Bruno Monteiro de Moura; Walan Robert da Silva (Revista Brasileira de Cineantropometria e Desempenho Humano, 2017)
The aim of the present study was to analyze the association between birthplace and relative age with winning Olympic medals in Brazilian athletes. he sample consisted of 186 Olympic medalist athletes born in Brazil. Data analysis was performed through descriptive (incidence and percentage) and inferential statistics (Chi-Square to binary logistic regression). he association between population contingents and Olympic champions presented a signiicant result (p <0.05); however, no signiicant associations were found with relative age. It was concluded that most Olympic medalists were born in places that present better living conditions, with intermediate MHDI, which appears only in cities with more than 100 thousand habitants, and relative age is not an important criterion in winning medals among athletes investigated.